X-ray studies on the mechanism of IPNS using substrate analogs - Long, A; Clifton, I; Roach, P; Schofield, C; Baldwin, J; Hajdu, J (1997)
The substrate analog L-S-(a-aminoadipoyl)-L-cysteinyl-glycine (ACG) was co-crystallised with isopenicillin N synthase using the hanging-drop vapourdiffusion method in an anaerobic environment. ' X-ray crystallography revealed a different mode of binding for ACG compared to the natural substrate, L-8-(